1980
DOI: 10.3109/00016358009003494
|View full text |Cite
|
Sign up to set email alerts
|

Thein vivoeffect of glucose solutions containing Cu+ +and Zn+ +on the acidogenicity of dental plaque

Abstract: A series of experiments were performed to evaluate the lowest concentration of copper or zinc effective in reducing the acidogenicity of dental plaque in vivo when applied simultaneously with a carbohydrate challenge. The effect of a combination of sub-effective concentrations of these metals was also determined. The results showed a significant reduction in acid production in plaque challenged with glucose solutions containing 0.25 mM CuSO4 or 5.0 mM Zn (C2H3O2).2 as compared to glucose solutions alone. Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…In addition, the inhibitory effect observed in the present study was associated with both copper and zinc, which could have given the single copper threshold an artificially low value. Afseth et al [1980] showed that copper and zinc have synergistic inhibitory effects on plaque acid production, possibly because they operate by a similar mechanism.…”
Section: Correlations Of Ions and Relative Bacterial Growth Ratesmentioning
confidence: 99%
“…In addition, the inhibitory effect observed in the present study was associated with both copper and zinc, which could have given the single copper threshold an artificially low value. Afseth et al [1980] showed that copper and zinc have synergistic inhibitory effects on plaque acid production, possibly because they operate by a similar mechanism.…”
Section: Correlations Of Ions and Relative Bacterial Growth Ratesmentioning
confidence: 99%
“…A number of early reports, however, suggest that copper cements are bactericidal [Smirnow, 1915] and it has been postulated that this effect is due to copper ion release. Copper ions are known to have a proven antibacterial and hence antiplaque effect, both in vitro on selected oral bacteria [Duguid, 1983;Morrier et al, 1998] and in vivo [Afseth, 1983;Afseth et al, 1980Afseth et al, , 1988, as well as anticaries activity in animal models [Afseth et al, 1984;Rosalen et al, 1996]. Given this background, the aims of this clinical trial were firstly, to determine the effect of a copper phosphate cement and a conventional glass ionomer on the bacteriological composition of carious dentine sealed under such restorations in vivo.…”
mentioning
confidence: 99%
“…Bates and Navia [1979] have shown in vitro that zinc sulphate reduced Streptococ cus mutans growth and initial plaque formation, but found no effect on preformed plaque. Human studies in which ZnCL was used as a mouthrinse have shown an inhibition of plaque formation [Skjorland et al, 1978] , or a decrease in plaque acidogenicity [Afseth et al, 1980]. Several bacterial enzymes require Zn3+ for activity such as DNA polymerase [Slater et al, 1971], and RNA polymerase [Miller et al, 1979], and methionyl t-RNA synthetase of Escherichia coli [Posorske et al, 1979] , Although stimulatory to the enzymes described above, zinc at 0.2 m M is inhibitory to Bacillus subtilis [Pickett and Dean, 1979] and to Klebsiella pneumo niae [Ba\dry et al, 1977].…”
mentioning
confidence: 99%